MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MELALUI VIDEO PEMBELAJARAN TEMA PERTUMBUHAN DAN PERKEMBANGAN MAKHLUK HIDUP PADA PEMBELAJARAN DARING DI SD NEGERI NAGRAK 02 - Sari, Putri Permata (CV Sintesia, 2025)
The implementation of this class action is carried out in two cycles. Each cycle has one meeting. After using learning media in the form of learning videos, student learning outcomes increased from the first cycle to the second cycle. This is evidenced by the improvements in the second cycle, which is indicated by the increase in changes in student behavior in the learning process by 12.5%, the increase in mastery of student learning outcomes by 29.55%, and the increase in the quality of the assessment of the implementation of learning by 13.4 %. From the results of the study, it can be concluded that through video learning, student learning outcomes can increase on the theme of growth and development of living things in class III C SD Negeri Nagrak 02 Sukaraja District, Bogor Regency.